Avaliação das condições de produção de fermentado acético de soro de leite - Bach, Fabiane (2012)
The whey is the source of liquid waste in the most important of cheese s making process. It has high organic load, due to the presence of 55% of the solid constituents of milk that gave it birth, as lactose, proteins, fat and minerals and their power is a hundred times more polluting than domestic sewage. The potential supply of carbohydrates and high quality functional proteins present in whey, justifies the use as raw material for the production of many value-added products. In this context, the objective of this study was to evaluate the variables involved in the preparation of alcoholic fermentation of whey to produce an alternative to using vinegar as whey discarded in the cheese s production. The methodology contemplated the execution of three stages: a) characterization of the generating source and raw material b) the alcoholic fermentation of whey and product s characterization c) acetous fermentation of fermented alcoholic and the product s characterization. A fractional factorial design with triplicate at the central point was prepared to carry out the alcoholic fermentation of whey. Four variables were evaluated: temperature, agitation, and the concentrations of the enzyme lactase and glucose added, of which only the concentration of added glucose showed significant and positive influence in the production of ethanol, for the confidence interval of 90%. New fermentations were carried out varying only the concentration of glucose added. The fermented alcohols were used as raw material for acetic fermentation. Quantification of acetic acid produced was carried out in liquid chromatography. All fermented showed production of acetic acid, but only the test made with the highest initial concentration of ethanol (6.34%) and produced by the methodology Orléans and Orléans Modified exceeded the minimum concentration of acetic acid required by Brazilian legislation. In this way was identified the influence of the main variables in the production of vinegar of the whey.